Blood levels of PAF are elevated during induction of immune complex mediated enteropathy in the rat - K. J. Bloch; B. P. Ng; M. Bloch (Hindawi Limited, 1992)
Intravenous injection into rats of immune complexes (IC) prepared in 5 × antigen excess rapidly induces annular bands of vascular congestion and transmural haemorrhage producing a striped appearance of the small intestine. Indirect evidence suggested a major role for PAF in the induction of lesions. In the present study, we showed that blood and leukocyte levels of PAF were elevated in most rats injected 10 min earlier with sufficient IC to induce lesions of 3+ to 4+ intensity. There was no significant difference in the number of rats with elevated plasma levels of PAF. The possibility that changes in blood PAF levels might be mirrored at sites closer to the lesions was considered. The overall effect of PAF on the small intestine of the rats is to induce stasis of flow; the precise target of PAF in mediating this effect is unknown.